Extracurricular activities of Dutch University students and their effect on employment opportunities as perceived by both students and organizations. (24th November 2017) - Nuijten, Marleen P. J.; Poell, Rob F.; Alfes, Kerstin
Abstract : Research on biographical data suggests that recruiters draw inferences about candidates' abilities and attributes based on résumé information. However, few studies have explored students' attributions with regard to the experiences that are relevant in enhancing employment opportunities. The aim of the present study is to fill this gap by analyzing the effect of university students' extracurricular activities (ECAs) on their perceived employment opportunities. Specifically, we combine a large sample of students with recruiters from a wide range of sectors in the Netherlands. Students completed a questionnaire, while recruiters participated in an experiment and semi‐structured interviews. Students' expectations about the value of ECAs for their employment opportunities were found to be misaligned with recruiters' viewpoints. Students expected academic performance to be more relevant for employment opportunities than ECAs, whereas recruiters stated the opposite. Students expected an internship to be the most valued ECA, whereas most recruiters prioritized a board year and emphasized students' motivation and ability to demonstrate the learning gained from ECAs in general. Implications for further biodata research are discussed.